Gemcitabine in Bone Sarcoma Resistant to Doxorubicin-Based Chemotherapy. (2000) - Merimsky, Ofer; Meller, Isaac; Kollender, Yehuda; Issakov, Josephine; Flusser, Gideon; Inbar, Moshe
Abstract : Subjects and Methods: Seven patients with progressive localized or metastatic chemo-resistant osteosarcoma were treated by gemcitabine.The protocol included gemcitabine 1000 mg/m2/w for 7 consecutive weeks, followed by 1 week rest. If no progression was observed, maintenance by gemcitabine 1000 mg/m2/w for 3 weeks every 28 days was given until failure was clinically or radiologically evident. Results. The true objective response rate was 0%. However, disease stabilization and clinical benefit response were observed in five patients (70%) for 13–96 weeks. Discussion. Postponing the inevitable death with a relatively non-toxic treatment, is, in our opinion, an important issue especially in young patients.Thus it may be justified and warranted to investigate the activity of gemcitabine in a larger group of patients with bone sarcomas.